'British Values Are Also Values All Around the World': Teaching Fundamental British Values through a Human Rights Lens. (11th December 2020) - Struthers, Alison E.C.; Mansuy, Julie
Abstract: Since 2014, the promotion of Fundamental British Values (FBV) has been a requirement across formal schooling in England. The agenda has, however, faced criticism from various stakeholders. Much of this denunciation has been directed at the opaque nature of FBV, but the agenda is problematic for more concerning reasons. It is arguable that, in light of the current threat from ethno-nationalism, frameworks such as FBV that focus on a particular definition and formulation of national values run the risk of being interpreted in a manner that is exclusionary and liable to 'other' different ethnic groups in the classroom. The FBV framework furthermore overlooks the fact that the UK isalready subject to numerous international human rights obligations, including many that mandate the provision of holistic and effective human rights education at all levels of formal education. This article therefore draws upon the findings of a pilot study conducted with Year 5 learners in four primary schools in the West Midlands showing that teaching about human rights through the FBV agenda is possible, by linking discussion of values at the national level to broader human rights principles. Such an approach satisfies the government's desire for children to learn about FBV, whilst highlighting that these values also exist in a global context. This, in turn, is likely to be a more effective way of encouraging learners to be global citizens who will contribute to the building of a broader culture that is respectful of human rights.